Incidence Of Various Types Of Cleft Lip And Palate In Southern Kp, Pakistan - Aziz, Asif; Hassan, Tauseef ul; Ahmad, Manzoor (Journal of Neonatal Surgery, 2025)
Cleft lip and palate (CLP) is among the most frequent congenital malformations in the world and its incidence and its etiological factors are notable among different regions. The objective of this study was to study the patterns, socioeconomic and risk factors of CLP occurring in Southern KPK, Pakistan, in which consanguinity and maternal education were hypothesized to be the important risk factors for CLP. This study was conducted from July 2017 to June 2024 over 7 years. The retrospective cross sectional study analyzed 223 confirmed CLP cases in two Tertiary Care Hospitals in districts of Bannu and Dera Ismail Khan. Cleft types, laterality, gender distribution, parental consanguinity, maternal education, family history, among other predisposing factors, were meticulously collected on a data base. Of these CLP, 1.83 per 1,000 live births were encountered, with a predominance of cleft lip with palate (46.6%), cleft lip (34.9%) and cleft palate (18.5%). Most affected patients were males (61.6%), and the majority of clefts were left sided (57.5%). Notably, consanguinity emerged as a significant risk factor, present in 83% of cases, alongside a positive family history in 14.4%. Furthermore, in 21.2% of the patients there were associated congenital anomalies, mainly congenital heart defects, and almost 19% of the children were presented to hospitals later than the infancy. These findings emphasize the multifaceted nature of CLP in this region, which includes both genetic predisposition, maternal education, and socio-economic inequality. The study recommends targeted public health strategies like avoiding consanguineous marriages, and increased access to prenatal care to reduce CLP risk. For healthcare policy and optimization of outcomes of affected children in Southern KPK, region specific insights are very critical.